Curable two-component resin-based systems
A dual-curing resin system with a block copolymer and fillers addresses the limitations of existing hardened resins by providing high toughness, low viscosity, and rapid curing, ensuring effective encasement of electric motor components with low thermal expansion and high thermal conductivity.
Patent Information
- Application Number
- JP2021555187
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-11
- Filing Date
- 2020-04-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-04-09
AI Technical Summary
Existing hardened resin systems for encasing electric motor stators and rotors do not achieve optimal characteristics in terms of high-temperature resistance, fluidity, reactivity, and thermal expansion, making them unsuitable for efficient casting and enclosures.
A dual-curing component resin system comprising a block copolymer with silicone and organic blocks, aluminum oxide, and wollastonite fillers, which provides high toughness, low viscosity, and quick curing, without anhydride, to create a hardened product with high thermal conductivity and low thermal expansion.
The system achieves high toughness, low viscosity, and rapid curing, ensuring crack resistance and efficient thermal conductivity, suitable for casting complex motor components without anhydride, enabling effective encasement of electric motors.
Smart Images

Figure 0007623290000001
Abstract
Description
[Technical field]
[0001] technical field FIELD OF THE DISCLOSURE This disclosure relates to curable two-component resin-based systems, cured products obtainable therefrom, and uses thereof. [Background technology]
[0002] background Systems based on curable resins are widely known for various purposes. One very interesting purpose from the point of view of e-mobility is the use of such systems to encapsulate, usually by casting, the stators and / or rotors of electric motors.
[0003] Systems based on curable resins for such purposes have been known in the prior art for some time.
[0004] For example, US Pat. No. 5,399,633 describes epoxy cast stators as far back as 1958.
[0005] US Pat. No. 5,399,633 relates to a formulation for stator potting based on an anhydride curing method. Polyoxyalkyleneamines with >2000 g / mol are described as additives to improve the elasticity and strength of the resin.
[0006] US Pat. No. 5,399,633 and US Pat. No. 5,499,623 outline the concept of stator encapsulation but do not provide details on the resin system used.
[0007] Patent Document 5 discloses a resin made from a liquid diglycidyl ether of bisphenol A, Silicone® SH 5500 as an antifoaming agent, γ-glycidyloxypropyltrimethoxysilane, and acicular wollastonite, but does not disclose a composition containing a block copolymer having silicone and organic blocks.
[0008] 3, No. 1, pp. 1111-1115, 2003 describes stator encapsulation and generally discusses some concepts.
[0009] US Pat. No. 5,399,633 (not yet published) describes a system based on an epoxy resin, a polyoxyalkyleneamine as hardener and a silane.
[0010] However, none of the curable resin-based systems described in the prior art achieve optimal properties for a casting system for stator or rotor encapsulation. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] British Patent No. 930185 A Specification [Patent Document 2] German Patent Specification No. 41 32 982 A1 [Patent Document 3] Canadian Patent No. 206259760 U [Patent Document 4] German Patent No. 10 2016 200 186 A1 [Patent Document 5] U.S. Patent No. 6001902A [Patent Document 6] International Publication No. 2018 / 140576 A1 [Non-patent literature]
[0012] [Non-Patent Document 1] “Leichtbautechnologien im Automobilbau”(Siebenpfeiffer,Wolfgang:Leichtbautechnologien im Automobilbau:Werkstoffe-Fertigung-Konzepte;ISBN 978-3-658-04025-3;Springer-Verlag;6 December 2013;pages 34-37) Summary of the Invention [Problem to be solved by the invention]
[0013] Purpose of disclosure In view of the shortcomings of the prior art, the objective of the present disclosure is to provide a ceramic material having a thermal conductivity of >1.10 W / mK, a low coefficient of thermal expansion (CTE) of <21 ppm / K, and a thermal conductivity of >4 MPa m 0.5 The present invention provides an anhydride-free, curable, two-component resin-based system that achieves high critical stress intensity factors, excellent flow and rapid reactivity. [Means for solving the problem]
[0014] Disclosure Unless otherwise stated herein, technical terms used in connection with this disclosure shall have the meanings commonly understood by those of ordinary skill in the art. Further, unless otherwise required by context, singular terms shall include pluralities and plural terms shall include the singular.
[0015] All patents, published patent applications and non-patent publications mentioned in the specification are indicative of the level of skill of those skilled in the art to which this disclosure pertains. All patents, published patent applications and non-patent publications mentioned in any part of this application are expressly incorporated herein by reference in their entirety to the same extent as if each individual patent or publication was specifically and individually indicated by reference thereto to the extent that they are not inconsistent with this disclosure.
[0016] All of the compositions and / or methods disclosed herein can be made and carried out without undue experimentation in light of this disclosure.Although the compositions and methods of the present disclosure are described in terms of preferred embodiments, it will be apparent to those skilled in the art that changes may be applied to the compositions and / or methods and in the steps or sequence of steps of the methods described herein without departing from the concept, spirit and scope of the present disclosure.All such similar substitutions and modifications apparent to those skilled in the art are deemed to be within the spirit, scope and concept of the present disclosure.
[0017] As utilized in accordance with the present disclosure, the following terms, unless otherwise specified, shall be understood to have the following meanings:
[0018] The use of the terms "a" or "an," when used in conjunction with the terms "comprising," "including," "having," or "containing" (or variations of such terms), may mean "one," but is also consistent with the meaning of "one or more," "at least one," and "one or more than one."
[0019] Use of the term "or" is used to mean "and / or" unless expressly stated to refer to alternatives only and only where the alternatives are mutually exclusive.
[0020] Throughout this disclosure, the term "about" is used to indicate that a value includes the inherent variation of error for a quantitative device, mechanism, or method or the inherent variation that exists among the subjects being measured. For example, but not as a limitation, when the term "about" is used, the specified value to which it refers can vary by plus or minus 10 percent, or 9 percent, or 8 percent, or 7 percent, or 6 percent, or 5 percent, or 4 percent, or 3 percent, or 2 percent, or 1 percent, or one or more fractions therebetween.
[0021] It will be understood that the use of "at least one" includes one as well as any amount greater than one, including but not limited to 1, 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 100, etc. The term "at least one" may extend up to 100 or 1000 or more depending on the term to which it refers. Furthermore, the amount of 100 / 1000 should not be considered limiting, as the lower or upper limits may also produce satisfactory results.
[0022] As used herein, the terms "comprising" (and any form of comprising, such as "comprise" and "comprises"), "having" (and any form of having, such as "have" and "has"), "including" (and any form of including, such as "includes" and "include") or "containing" (and any form of containing, such as "contains" and contain) are inclusive or open-ended and do not exclude additional, unrecited elements or method steps.
[0023] The phrases "or combinations thereof" and "and combinations thereof" as used herein refer to all permutations and combinations of the listed items preceding said term. For example, "A, B, C or combinations thereof" is intended to include at least one of: A, B, C, AB, AC, BC or ABC, and also BA, CA, CB, CBA, BCA, ACB, BAC or CAB, if order is important in the particular context. Continuing with this example, combinations including repeats of one or more items or terms, such as BB, AAA, CC, AABB, AACC, ABCCCC, CBBAAA, CABBB, etc., are expressly included. One of ordinary skill in the art will understand that there is typically no limit to the number of items or terms in any combination, unless otherwise clear from the context. In the same spirit, the terms "or combinations thereof" and "and combinations thereof" when used in conjunction with the phrase "selected from" or "selected from the group consisting of" refer to all permutations and combinations of the listed items preceding the phrase.
[0024] Phrases such as "in one embodiment," "in an embodiment," "according to one embodiment," and the like generally mean that the particular feature, structure, or characteristic following the phrase is included in at least one embodiment of the disclosure, and may be included in more than one embodiment of the disclosure. Importantly, such phrases are open-ended and do not necessarily refer to the same embodiment, but of course can refer to one or more prior and / or subsequent embodiments. For example, in the appended claims, any of the claimed embodiments can be used in any combination.
[0025] This disclosure (a) a resin component comprising (i) at least one epoxy resin, (ii) a block copolymer comprising silicone and organic blocks, (iii) a silane, and (iv) a filler comprising aluminum oxide and wollastonite; (b) a curing agent component comprising at least one polyoxyalkylene polyamine wherein the curable system comprises a total of >60 wt. % filler having a wollastonite to aluminum oxide ratio of 50 to 75 wt. % and 25 to 50 wt. % aluminum oxide, and wherein the hardener component (b) does not comprise any anhydrides.
[0026] Systems based on two-component curable resins, where the curable system contains >60 wt. % filler in total, are characterized by higher fracture toughness K1C and G1C, shorter gel times, and require shorter cure times.
[0027] In one embodiment of the present disclosure, hardener component (b) also contains a filler comprising aluminum oxide and wollastonite. Thus, in this embodiment, both resin component (a) and hardener component (b) each contain a filler comprising aluminum oxide and wollastonite (a), where the filler in resin component (a) is preferably, but not necessarily, the same as the filler in hardener component (b).
[0028] In a further embodiment, the curable system comprises >70 wt.% total filler, which enables the curable two-component resin-based system to exhibit particularly short gel times and, upon further curing, low coefficient of thermal expansion CET (below Tg) and high thermal conductivity.
[0029] In another embodiment, the curable system comprises more than 60 wt.% but less than 70 wt.% total filler, which allows the curable two-component resin-based system to exhibit high fluidity (low viscosity) and, upon curing, a particularly high elongation at break.
[0030] In a preferred embodiment, the ratio of wollastonite to aluminum oxide in the system is 60 to 70% by weight wollastonite and 30 to 40% by weight aluminum oxide, respectively, and preferably about 2 / 3 wollastonite and about 1 / 3 aluminum oxide by weight.
[0031] In one embodiment of the present disclosure, the aluminum oxide and wollastonite each independently have an average particle size D50 of 0.1 μm to 60 μm, preferably 2 to 20 μm, most preferably 4 to 6 μm (for aluminum oxide) and 5 to 15 μm for wollastonite.
[0032] Preferably, the resin component (a) comprises the block copolymer in an amount of 0.3% to 10% by weight, preferably 1% to 4% by weight.
[0033] In a further embodiment, the resin component (a) comprises the silane in an amount of 0.01% to 4% by weight, preferably 0.1% to 1% by weight.
[0034] In another embodiment of the present disclosure, the resin composition (a) comprises at least one polyoxyalkylene polyamine in an amount of 5% to 50% by weight, preferably 10% to 25% by weight.
[0035] In a further embodiment, the hardener component (b) comprises at least one wetting agent.
[0036] In a preferred embodiment, the at least one wetting agent is a copolymer having acidic groups.
[0037] In a particularly preferred embodiment, the hardener component (b) comprises at least one wetting agent in an amount of 0.2% to 10% by weight, preferably 1% to 2.5% by weight.
[0038] A ratio of 100 pbw of resin component (a) to 50 to 100 pbw, preferably 60 to 70 pbw, and most preferably about 67 pbw of hardener component (b) is preferred.
[0039] The present disclosure also relates to cured products obtainable by curing the above-described curable systems.
[0040] To obtain the cured product of the present disclosure, the curable system is preferably cured at 120° C. for a period of time not greater than 4 hours, preferably not greater than 2 hours at 120° C.
[0041] In one embodiment, the product exhibits an elongation at break of >0.5% elongation, preferably >1% elongation, measured according to ISO 527.
[0042] In another embodiment, the product has a strength of >2.6 MPa m as measured by double torsion test (PM 216-0 / 89, dimensions of test species: 80x34x4 mm; test speed: 0.50 mm / min). 0.5 Fracture toughness K 1C and >700 J / m 2 G 1C , preferably >4MPa m 0.5 K 1C and >1000J / m 2 G 1C Shows.
[0043] In a preferred embodiment, the product exhibits a thermal conductivity measured according to ISO 8894-1 of >0.7 W / mK, preferably >1 W / mK.
[0044] In a further embodiment, the article exhibits a coefficient of thermal expansion (CTE) measured according to ISO 11359-2 of <35 ppm / K, preferably <21 ppm / K.
[0045] The present disclosure also relates to the use of the above cured products for electrical applications, in particular for encapsulating the stator and / or rotor of an electric motor.
[0046] Surprisingly, the particular combination of features of the present disclosure results in the achievement of the properties necessary to obtain an improved casting system for the encapsulation of the stators and / or rotors of electric motors.
[0047] The epoxy resin used for the curable system of the present disclosure is not limited to any particular type and may be any type of epoxy resin. The epoxy resin may be, for example, a polyglycidyl ether, a cycloaliphatic epoxy resin, an N-glycidyl compound, or a combination thereof.
[0048] The polyglycidyl ether may for example be selected from the group consisting of bisphenol-A-diglycidyl ether, bisphenol-F-diglycidyl ether, 2,2-bis(4-hydroxy-3-methylphenyl)propane-diglycidyl ether, bisphenol-E-diglycidyl ether, 2,2-bis(4-hydroxyphenyl)butane-diglycidyl-ether, bis(4-hydroxyphenyl)-2,2-dichloro-ethylene, bis(4-hydroxyphenyl)diphenylmethane-diglycidyl ether, 9,9-bis(4-hydroxyphenyl)fluorene-diglycidyl ether, 4,4'-cyclohexylidenebisphenol-diglycidyl-ether, epoxy phenol novolacs and epoxy cresol novolacs.
[0049] Alicyclic epoxy resins are, for example, bis(epoxycyclohexyl)-methylcarboxylates. diglycidyl ether, bis(4-hydroxy-cyclohexyl)methane-diglycidyl ether, 2,2-bis(4-hydroxy-cyclohexyl)propane-diglycidyl ether, tetrahydrophthalic acid-diglycidyl ester, hexahydrophthalic acid-diglycidyl ester, 4-methyltetrahydrophthalic acid-diglycidyl ester, and 4-methylhexahydrophthalic acid-diglycidyl ester.
[0050] The N-glycidyl compound may be selected, for example, from the group consisting of N,N,N',N'-tetraglycidyl-4,4'-methylene-bis-benzenamine, N,N,N',N'-tetraglycidyl-3,3'-diethyl-4,4'-diamino-diphenylmethane, 4,4'-methylene-bis[N,N-bis(2,3-epoxypropyl)aniline] and 2,6-dimethyl-N,N-bis[(oxiran-2-yl)methyl]aniline.
[0051] Particularly preferred epoxy resins are polyglycidyl ethers based on bisphenols, such as bisphenol-A-diglycidyl ether.
[0052] Any silane suitable for use with epoxy resins may be incorporated into resin component (a). Epoxy-functional silanes may be selected because of their particularly high compatibility with epoxy resins.
[0053] As block copolymers having silicone and organic blocks (the organic blocks are based, for example, on caprolactone or other lactones), preferably compounds such as Genioperl® W35 (Wacker Chemie AG, Munich, Germany) may be used.
[0054] Extensive experimentation has shown that the use of specific combinations of filler components, both in the resin component and in the hardener, is essential to achieve the specific properties of the products of the present disclosure. The specific fillers of the present disclosure include, and preferably consist of, aluminum oxide and wollastonite, where the ratio of wollastonite to aluminum oxide is 50 to 75% by weight, preferably 60 to 70% by weight, wollastonite and 25 to 50% by weight, preferably 30 to 40% by weight, aluminum oxide. Most preferably, the ratio of wollastonite to aluminum oxide in the system is about 2 / 3 wollastonite and about 1 / 3 aluminum oxide by weight.
[0055] The curing agent in hardener component (b) can be any polyoxyalkylene polyamine suitable for curing epoxy resin compositions. Examples are the polyoxyalkylene diamines, polyoxyalkylene triamines and polyoxyalkylene polyamines sold under the trade name JEFFAMINE® available from Huntsman Corp. or its affiliates, The Woodlands, TX. Preferred curing agents are polyoxyalkylene diamines having a molecular weight of 400 g / mole or less.
[0056] Another essential component of the disclosed system is at least one wetting agent. Preferred examples are copolymers containing acidic groups such as those available from Byk, such as Byk W 9010, W 995 and W 996.
[0057] Further additives such as anti-settling agents, colorants, fumed silica and / or fumed alumina, etc. may be added to both components (a) and (b). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0058] Working Example Further details and advantages will become apparent from the following examples. All portions are available from Huntsman Corp. or its affiliates (with exceptions as indicated) and are as follows:
[0059] Reactants Araldite MY 740: Bisphenol-A diglycidyl ether epoxy resin with an epoxy equivalent weight of 180-190 g / eq. Silane A 187: [3-(2,3-epoxypropoxy)propyl]trimethoxysilane; Supplier: Momentive Genioperl W35: block copolymer with silicone and organic blocks; Supplier: Wacker Aerosil 200: hydrophilic fumed silica; Supplier: Evonik Byk 7410 ET: Rheological additive (anti-settling agent); Supplier: Byk Alumina CL 4400 FG: Calcined aluminum oxide with a D50 of 5.2 microns and a BET of 60 m2 / g, Supplier: Almatis, Germany Wollastonite: Calcium metasilicate (Ca3Si3O9) with the following specifications: Particle size D50 9-16 microns <45 microns 84±5% by weight <4 microns 26-36% by weight <2 microns <28% by weight Bulk density 0.88-0.97g / cm 3 Luminance, Ry>85% L / D ratio: 3:1 Supplier: Nordkalk,Finland Aeroxide Alu C: Fumed alumina; Supplier: Evonik DW0137-1: Black paste (carbon black in epoxy resin) JEFFAMINE D 230: Polyoxypropylenediamine BYK W 9010: Rheological additive (wetting agent); Supplier: Byk Cab-O-Sil TS 720: Hydrophobic fumed silica; Supplier: Cabot BYK W 940: Rheological additive (anti-settling agent); Supplier: Byk Araldite CW 229-3: The resin component of a commercially available very tough system based on bisphenol-A epoxy. Araldite HW 229-1: A commercially available hardener component of a very tough system based on methyl-tetrahydrophthalic anhydride. Araldite CW 30334: Resin component of a commercially available system based on bisphenol-A epoxy, intended for stator potting and having a thermal conductivity of 1.1-1.2 W / mK Aradur HW 30335: hardener component of a commercially available system based on methyl-tetrahydrophthalic anhydride, intended for stator potting and having a thermal conductivity of 1.1-1.2 W / mK Araldite CW 30039: A one-component epoxy system based on cycloaliphatic resins commercially available for rotor potting and with a very low CTE
[0060] method The elongation at break is according to ISO 527, the fracture toughness K 1C and G 1C is double torsion test (PM 216-0 / 89, test type dimensions: 80x34x4mm; test speed: 0.50mm / min), thermal conductivity was measured according to ISO 8894-1 and coefficient of thermal expansion (CTE) according to ISO 11359-2.
[0061] Comparative Example 1 300 g of Araldite CW 229-3 and 300 g of Araldite HW 229-1 are heated to 50° C. separately and then mixed with a propeller stirrer for 5 minutes. The mixture is then degassed in a vacuum chamber at about 1 mbar. The material is then poured into a metal mold (preheated to 80° C.) to prepare a plate for testing. The mold is then placed in an oven and the material is cured at 80° C. for 6 hours and at 140° C. for 10 hours. After cooling, the plate obtained after demolding is cut into standard test specimens to determine Tg, CTE, K1C, G1C, flexural and tensile strength, and thermal conductivity. The test results are shown in Table 1.
[0062] Comparative Example 2 300 g of Araldite CW 30334 and 300 g of Aradur HW 30335 are heated to 50° C. separately and then mixed with a propeller stirrer for 5 minutes. The mixture is then degassed in a vacuum chamber at about 1 mbar. The material is then poured into a metal mold (preheated to 80° C.) to prepare the plate for testing. The mold is then placed in an oven and the material is cured at 95° C. for 2 hours and at 95-130° C. for 1 hour, then at 130° C. for 2 hours. After cooling, the plate obtained after demolding is cut into standard test specimens to determine Tg, CTE, K1C, G1C, flexural and tensile strength, and thermal conductivity. The test results are shown in Table 1.
[0063] Comparative Example 3 400 g of Araldite CW 30039 are heated to 60° C. and stirred with a propeller stirrer for 5 minutes. The material is then degassed in a vacuum chamber at about 1 mbar. The material is then poured into a metal mold (preheated to 80° C.) to prepare the plate for testing. The mold is then placed in an oven and the material is cured at 120° C. for 1 hour and at 180° C. for 1.5 hours. After cooling, the plate obtained after demolding is cut into standard test specimens to determine Tg, CTE, K1C, G1C, flexural and tensile strength, and thermal conductivity. The test results are shown in Table 1. EXAMPLES
[0064] Resin component (a) is prepared as follows:
[0065] 321.2 g of Araldite MY 740 and 21.13 g of Genioperl W35 are placed in a mixer (with anchor stirrer and dispersing blades) and then heated to 80° C. with mixing for 30 minutes (until the Genioperl W35 is fully dissolved) using the anchor stirrer at 60 rpm.
[0066] Then 5.28 g of DW 0137-1 is added and the mass is cooled to 50° C. with further stirring.
[0067] Then 1.76 g of Silane A 187 and 2.52 g of Byk 7410 ET are added to the mass and mixed for 3 minutes at 240 rpm.
[0068] Then 179.61 g of Alumina CL 4400 FG is added and mixed for 5 minutes at 240 rpm.
[0069] Then 17.61 g of Aeroxide Alu C is added to the mixture in three portions, followed by 1.76 g of Aerosil 200, mixing each time for 5 minutes at 240 rpm at 50°C.
[0070] Then 445.6 g of Wollastonite are added in 4 portions, mixing each time for 5 minutes with the anchor stirrer at 240 rpm and with the dispersing blade at 400 rpm.
[0071] Finally, any fillers that are not yet wetted are scraped down into the mixture and then the whole mass is mixed under vacuum for 15 minutes with a dispersing blade at 400 rpm and with an anchor stirrer at 240 rpm.
[0072] The hardener component (b) is prepared as follows:
[0073] 141.02 g of JEFFAMINE® D 230 and 20 g of Byk W The 9010 is placed in a mixer (with anchor agitator and disperser blades) and then heated to 90°C with mixing for 20 minutes with the anchor agitator at 240 rpm, then cooled to 50°C.
[0074] Then 256.86 g of Alumina CL 4400 FG is added and mixed for 5 minutes using an anchor stirrer at 240 rpm.
[0075] Then 25.18 g of Aeroxide Alu C is added to the mixture in three portions. Then 5.0 g of Cab-O-Sil TS 720 is added, mixing each time for 5 minutes with an anchor stirrer at 240 rpm at 50°C.
[0076] Then 1 / 4 of 544.94g of Wollastonite is added and mixed for 5 minutes at 50°C with an anchor stirrer at 240 rpm and a disperser blade at 400 rpm.
[0077] Then 7.0 g Byk W 940 are added and stirred for 5 minutes with an anchor stirrer at 240 rpm and a disperser blade at 400 rpm.
[0078] Then 3 / 4 of 544.94g of Wollastonite is added in 3 portions and mixed for 5 minutes at 50°C with an anchor stirrer at 240 rpm and a disperser blade at 400 rpm.
[0079] Finally, any fillers that are not yet wetted are scraped down into the mixture and then the whole mass is mixed under vacuum for 15 minutes with a dispersing blade at 400 rpm and with an anchor stirrer at 240 rpm.
[0080] Preparation of the final mixture of (a) and (b) 100 g of premix (a) (adjusted to 50° C.) and 67 g of premix (b) (adjusted to 50° C.) are mixed for about 5 minutes with an anchor stirrer at 240 rpm and then degassed under vacuum.
[0081] The reaction mixture of (a) and (b) is then poured into a metal mold (preheated to about 80° C.) to prepare the test specimens. The mold is then placed in an oven and the material is cured at 120° C. for 2 hours.
[0082] After cooling to room temperature, the test specimens were demolded and prepared for measurement of, e.g., mechanical data. The test results are shown in Table 1.
[0083] The parameters are then determined under standard conditions as shown in Table 1. EXAMPLES
[0084] Resin component (a) was prepared as in Example 1. Pure (specifically unfilled) JEFFAMINE® D 230 was used as hardener component (b). A final mixture of (a) and (b) was prepared in an amount of 9.5 pbw JEFFAMINE® D 230(b) per w resin (a) and processed as in Example 1. [Table 1]
[0085] Comparison of the system of Example 1 with three comparative examples highlights several competing objectives of the present disclosure. This highlights the unusually high performance of the disclosed system since it combines: 1. Excellent fluidity (as indicated by a viscosity of less than 3 Pas at 80°C) 2. Short curing time (only 2 hours) at moderate temperatures (120°C) 3. Extremely high toughness (K1C>4MPa.m 1 / 2 and >1000L / m 2 G1C 4. Elongation at break >1% 5.CTE <21ppm / K 6. Thermal conductivity >1W / mK 7. Free of anhydrides.
[0086] The combination of low CTE and excellent toughness makes the disclosed system very useful for encapsulation of critical stators and / or rotors where metal edges may crack during temperature changes. It can flow into tight gaps, provides the necessary thermal conductivity, and cures quickly. Thus, the disclosed system is fully applicable to the automatic pressure gelation (APG) process even without post cure, depending on the geometry and thermal and timing conditions.
[0087] The system of Comparative Example 1 is a widely used very tough epoxy system based on wollastonite filler. The system provides very high (but low toughness compared to the system of the present disclosure) and excellent flowability. However, it does not deliver very low CTE, the thermal conductivity is not as good as necessary, and it requires much longer cure time.
[0088] The system of Comparative Example 2 is aimed at producing the desired thermal conductivity of >1.1 W / mK. It also provides excellent flowability. However, the toughness is lower compared to Example 1, the CTE is significantly higher, and it requires more severe curing conditions.
[0089] Because the CTE for the systems of Comparative Examples 1 and 2 is significantly higher, there are stresses due to the mismatch of the CET of the epoxy to the metal parts that may lead to cracking under thermal cycling conditions that cannot be handled by the available toughness quality of these systems. Thus, the combination of poorer CTE and poorer toughness (in the systems of Comparative Examples 1 and 2) may lead to a higher risk of cracking.
[0090] The system of Comparative Example 3 is an anhydride-free epoxy system, which gives a very low CTE and thus produces low stress during application. However, it lacks toughness compared to the system of the present disclosure, its thermal conductivity is much lower, and the curing requires much harsher conditions. Finally, the flow is not as good due to the higher viscosity.
[0091] The subject matter disclosed above should be considered as illustrative and not limiting, and the appended claims are intended to cover all such modifications, enhancements and other embodiments that fall within the true scope of the invention. Thus, the scope of the invention should be determined by the broadest permissible interpretation of the following claims and their equivalents to the maximum extent permitted by law, and should not be limited or restricted by the above detailed description.
Claims
1. (a) a resin component comprising: (i) at least one epoxy resin which is a polyglycidyl ether; (ii) a block copolymer comprising silicone and lactone-based organic blocks; (iii) an epoxy-functional silane; and (iv) a filler comprising aluminum oxide and wollastonite; and (b) a hardener component comprising: (i) at least one polyoxyalkylene polyamine; and (ii) a filler comprising aluminum oxide or wollastonite. %. wherein the curable system comprises a total of >60 wt. % filler having a wollastonite to aluminum oxide ratio of 50-75 wt. % and 25-50 wt. % aluminum oxide, and wherein the hardener component (b) does not contain any anhydrides.
2. 10. The hardenable system of claim 1, wherein the hardener component (b) also comprises a filler comprising aluminum oxide and wollastonite.
3. 3. The hardenable system of claim 2, wherein the hardenable system comprises >70 wt. % in total of filler.
4. 4. A hardenable system according to any one of claims 1 to 3, wherein the ratio of wollastonite to aluminium oxide in the system is 60 to 70% by weight wollastonite and 30 to 40% by weight aluminium oxide, respectively.
5. 5. A hardenable system according to any one of claims 1 to 4, wherein the aluminium oxide and the wollastonite each independently have an average particle size D50 of 0.1 μm to 60 μm.
6. 6. The curable system of claim 1, wherein the resin component (a) comprises a block copolymer in an amount of from 0.3% to 10% by weight.
7. 7. A curable system according to any one of claims 1 to 6, wherein the resin component (a) comprises the silane in an amount of from 0.01% to 4% by weight.
8. 8. The curable system of claim 1, wherein the curable component (b) comprises at least one polyoxyalkylene polyamine in an amount of from 5% to 50% by weight.
9. A cured product obtainable by curing a curable system according to any one of claims 1 to 8.
10. 10. The cured product of claim 9, wherein the curable system is cured at 120°C for a period of 4 hours or less.
11. 11. The cured product of claim 9 or 10, wherein the product exhibits an elongation at break of > 0.5% elongation measured according to ISO 527.
12. 12. The cured product of any one of claims 9 to 11, wherein the product exhibits a fracture toughness K1C of > 2.6 MPa m0.5 and a G1C of > 700 J / m2, measured by double torsion test (PM 216-0 / 89, test type dimensions: 80x34x4 mm; test speed: 0.50 mm / min).
13. 13. The cured product of any of claims 9 to 12, wherein the product exhibits a thermal conductivity of >0.7 W / (mK) measured according to ISO 8894-1.
14. 14. The cured product of any of claims 9 to 13, wherein the product exhibits a coefficient of thermal expansion (CTE) of < 35 ppm / K measured according to ISO 11359-2.
15. 15. Use of the cured product according to any one of claims 9 to 14 for electrical applications.
Citation Information
Patent Citations
CA206259760U
electric machine
DE102016200186A1
Additives improving elasticity and strength of epoxy] resins for stators - comprising polyoxyalkylene amine(s) and opt. also poly:alkylene glycol(s) and / or thermoplastic phenoxy] resins
DE4132982A1
Improvements in dynamo-electric machines and methods of manufacture for same
GB930185A
JP1974089800A